AUTOMATION OF THE HEATING, VENTILATION AND AIR CONDITIONING (HVAC) SYSTEM OF AN ADMINISTRATIVE BUILDING (Ustozlar uchun, 2026)
This article scientifically examines the automation of the heating, ventilation, and air conditioning (HVAC) system of an administrative building. Problem: under conventional thermostat-based control, room temperatures fluctuate within ±2.5°C, and 32–38% of energy consumption is wasted heating/cooling unoccupied rooms. Method: a centralized Building Management System (BMS) was developed based on Siemens Desigo PXC controllers, temperature/CO₂/humidity sensors, and variable air volume (VAV) dampers; occupancy-based scheduling and cascade PID control were applied. Result: temperature was maintained at ±0.5°C accuracy and CO₂ levels were kept within 800–1000 ppm. Conclusion: annual energy consumption decreased by 27.6%, heating/cooling costs dropped from 124,600 to 90,200 thousand UZS, and occupant comfort (PMV index) improved significantly.